CD155/SRC complex promotes hepatocellular carcinoma progression via inhibiting the p38 MAPK signalling pathway and correlates with poor prognosis. Issue 4 (5th April 2022) - Jin, An‐Li; Zhang, Chun‐Yan; Zheng, Wen‐Jing; Xian, Jing‐Rong; Yang, Wen‐Jing; Liu, Te; Chen, Wei; Li, Tong; Wang, Bei‐Li; Pan, Bai‐Shen; Li, Qian; Cheng, Jian‐Wen; et al.
Abstract: Background: Hepatocellular carcinoma (HCC) is a prevalent malignancy with poor prognosis. As a cell adhesion molecule, poliovirus receptor (PVR/CD155) is abnormally overexpressed in tumour cells, and related to tumour proliferation and invasion. However, the potential role and mechanism of CD155 have not yet been elucidated in HCC. Methods: Immunohistochemistry, RT‐PCR and Western blot assays were used to determine CD155 expression in HCC cell lines and tissues. Cell Counting Kit‐8 and colony formation assays were used to examine cell proliferation. Transwell and wound healing assays were used to evaluate cell migration and invasion. Cell apoptosis and cycle distribution were assessed by flow cytometry. Cox regression and Kaplan–Meier analyses were performed to explore the clinical significance of CD155. The role of CD155 in vivo was evaluated by establishing liver orthotropic xenograft mice model. RNA sequencing, bioinformatics analysis and co‐immunoprecipitation assay were used to explore the downstream signalling pathway of CD155. Results: CD155 was upregulated in HCC tissues and represented a promising prognostic indicator for HCC patients ( n = 189) undergoing curative resection. High CD155 expression enhanced cell proliferation, migration and invasion, and contributed to cell survival in HCC. CD155 overexpression also induced epithelial–mesenchymal transition in HCC cells. CD155 function in HCC involved SRC/p38 MAPK signalling pathway. CD155 interacted with SRC homology‐2 domain of SRC and promoted SRC activation, further inhibiting the downstream p38 MAPK signalling pathway in HCC. Conclusions: CD155 promotes HCC progression via the SRC/p38 MAPK signalling pathway. CD155 may represent a predictor for poor postsurgery prognosis in HCC patients. Abstract : CD155 is highly expressed in hepatocellular carcinoma (HCC) tissues, and its overexpression predicts poor postsurgery prognosis in HCC patients. CD155 promotes HCC progression via its cell‐intrinsic role in regulating cell proliferation, migration, invasion and epithelial–mesenchymal transition (EMT). CD155 enhances SRC activation through interacting with SH2 domain of SRC, further inhibiting the downstream p38 MAPK signalling pathway in HCC.